2019
DOI: 10.5505/pajes.2018.04496
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the effect of binding material and Thiobacillus thiooxidans on the heavy metals mobilization in the mine tailings

Abstract: Çalışmada, terk edilmiş bir Pb-Zn madeni ve işletilmekte olan bor madeni atıklarındaki arsenik (As), bor (B), kadmiyum (Cd), bakır (Cu), mangan (Mn), kurşun (Pb), talyum (Tl) ve çinko (Zn) elementlerinin toplam konsantrasyonları, kimyasal bağlanma formlarındaki dağılımları ile bu elementlerin bağlayıcı materyal ve asidik bakteri olan Thiobacillus thiooxidans varlığında mobilizasyonları incelenmiştir. Ayrıca atık ve bağlayıcı materyallerdeki sülfür ve karbonat miktarları da belirlenerek, statik testlere göre at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…It was found that the interaction between Cu­(II) and Fe­(II) stimulates the reduction process of heterogeneous iron in organic matter, and a high dose of CuO NPs promotes the electron transfer process. Thiobacillus was found in high-As sediments and had an influence on As release, and the existence of Thiobacillus thiooxidans increased metal mobility. Iron-reducing bacteria such as Anaeromyxobacter , Geothrix , and Geobacter could promote Fe and As reduction by boosting extracellular electron transfer, and Paludibaculum could also promote dissimilatory Fe­(III) reduction. In this study, the abundance of Fe­(III)-reducing and sulfur-oxidizing bacteria such as Anaeromyxobacter , Paludibaculum , Geothrix , and Thiobacillus was decreased when exposed to 100 mg kg –1 CuO NPs, thereby decreasing As availability in the soil. Moreover, the RDA and correlation analysis demonstrated that the decrease in soil pH, DOC, and available As was related to the decrease in Fe­(III)-reducing and sulfur-oxidizing bacteria under the 100 mg kg –1 CuO NP treatment (Figure S13).…”
Section: Discussionmentioning
confidence: 68%
“…It was found that the interaction between Cu­(II) and Fe­(II) stimulates the reduction process of heterogeneous iron in organic matter, and a high dose of CuO NPs promotes the electron transfer process. Thiobacillus was found in high-As sediments and had an influence on As release, and the existence of Thiobacillus thiooxidans increased metal mobility. Iron-reducing bacteria such as Anaeromyxobacter , Geothrix , and Geobacter could promote Fe and As reduction by boosting extracellular electron transfer, and Paludibaculum could also promote dissimilatory Fe­(III) reduction. In this study, the abundance of Fe­(III)-reducing and sulfur-oxidizing bacteria such as Anaeromyxobacter , Paludibaculum , Geothrix , and Thiobacillus was decreased when exposed to 100 mg kg –1 CuO NPs, thereby decreasing As availability in the soil. Moreover, the RDA and correlation analysis demonstrated that the decrease in soil pH, DOC, and available As was related to the decrease in Fe­(III)-reducing and sulfur-oxidizing bacteria under the 100 mg kg –1 CuO NP treatment (Figure S13).…”
Section: Discussionmentioning
confidence: 68%